(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Continuous application of N alone or in combination with P and K during 4 years period did not influence soil pH significantly over control. pH value of soil after harvesting of crop year after year were comparable. The relative values of soil pH during experimentation period varied from 98-101 over initial pH value assuming as 100. Ec and Organic Carbon of soil generally increased. Maximum increase in Ec was seen under combined application of NPK and minimum under no fertilizer. The magnitude of increases in Ec being in the order of 8, 16 and 22 percent and organic carbon content of soil improved by 4, 5 and 9 percent under N, NP, and NPK treatments, respectively.Intensive use of fertilizers, intensive cropping and high yielding seeds have no doubt brightened the hopes of humanity for successfully meeting the challenge of food shortage but it has also brought into the sharp focus numerous problem of soil fertility, fertilizer, soil and water management. Soil fertility is considered in the past in a restricted sense as a physico-chemical phenomenon or as an index of available nutrients for plants, but the modern usage of the term cannot the capacity of the soil produce crops of economic value to man and maintain the health of the soil for future use. An integrated application of fertilizer showed better response in long term nutrient experiment in soil (Prasad et-al 1995). Thus, any system of management of soil fertility will ultimately consider all aspects of soil-plant relationship and pollution of the environment as well.